Permanent neonatal diabetes mellitus: prevalence and genetic diagnosis in the SEARCH for Diabetes in Youth Study. Issue 3 (10th October 2012) - Kanakatti Shankar, Roopa; Pihoker, Catherine; Dolan, Lawrence M.; Standiford, Debra; Badaru, Angela; Dabelea, Dana; Rodriguez, Beatriz; Black, Mary Helen; Imperatore, Giuseppina; Hattersley, Andrew; Ellard, Sian; Gilliam, Lisa K.; et al.
Abstract : Background: Neonatal diabetes mellitus (NDM) is defined as diabetes with onset before 6 months of age. Nearly half of individuals with NDM are affected by permanent neonatal diabetes mellitus (PNDM). Mutations in KATP channel genes ( KCNJ11, ABCC8 ) and the insulin gene ( INS ) are the most common causes of PNDM. Objective: To estimate the prevalence of PNDM among SEARCH for Diabetes in Youth (SEARCH) study participants (2001–2008) and to identify the genetic mutations causing PNDM. Methods: SEARCH is a multicenter population‐based study of diabetes in youth <20 yr of age. Participants diagnosed with diabetes before 6 months of age were invited for genetic testing for mutations in the KCNJ11, ABCC8, and INS genes. Results: Of the 15, 829 SEARCH participants with diabetes, 39 were diagnosed before 6 months of age. Thirty‐five of them had PNDM (0.22% of all diabetes cases in SEARCH), 3 had transient neonatal diabetes that had remitted by 18 months and 1 was unknown. The majority of them (66.7%) had a clinical diagnosis of type1 diabetes by their health care provider. Population prevalence of PNDM in youth <20 yr was estimated at 1 in 252 000. Seven participants underwent genetic testing; mutations causing PNDM were identified in five (71%), (two KCNJ11, three INS ). Conclusions: We report the first population‐based frequency of PNDM in the US based on the frequency of PNDM in SEARCH. Patients with NDM are often misclassified as having type1 diabetes. Widespread education is essential to encourage appropriate genetic testing and treatment of NDM.